Peran generasi muda dalam memperkuat demokrasi di indonesia - HARAHAP, RAMZY AR RASYID (Maliki Interdisciplinary Journal, 2026)
Democracy is a system of government that places public participation as a crucial element in determining the direction of state policy. In the development of democracy in Indonesia, the younger generation plays a strategic role as agents of social and political change. This article aims to discuss the role of the younger generation in strengthening democracy in Indonesia, the challenges they face, and efforts that can be made to increase their participation in democratic life. The method used in writing this article is a literature study by reviewing various journals and relevant scientific sources on democracy and youth participation. The results of the discussion indicate that the younger generation plays a significant role in increasing political participation, utilizing social media as a means of democratic communication, and countering hoaxes and disinformation in the digital era. Furthermore, the younger generation also contributes to maintaining democratic values ​​through a critical, participatory, and responsible attitude towards social and political life. However, the younger generation still faces various challenges such as low political literacy, the influence of identity politics, the spread of fake news, and political pragmatism. Therefore, political education, strengthening digital literacy, and support from the government and educational institutions are needed so that the younger generation can optimally fulfill their role in strengthening democracy in Indonesia.